LOGISTIK AN DER GERMANISTIK – WARUM NICHT? EIN PLÄDOYER FÜR DEN FACHSPRACHENUNTERRICHT AN DER UNIVERSITÄT - Strzelecka, Grażyna (Neofilolog, 2018)
Not often do we encounter a specialized foreign language course at a university humanities department. However, why should foreign language students not be provided with practical knowledge which may be useful in future professional life? The article presents an experiment conducted with the participation of MA students of German studies at Warsaw University. The aim is to teach language skills, as well as convey professional knowledge in the CLIL formula, which is becoming more and more popular. It is consistent with requests of students themselves. Logistics is a useful introduction to various branches of the economy. Considering that the German language is becoming more and more important in business-related professions, the topics discussed in this course may be required in logistics, forwarding and other areas. In addition to traditional logistics topics, such as transport, storage and waste disposal, we also discuss topics such as business correspondence or negotiations and practice translations.